Aqueous and Air‐Compatible Fabrication of High‐Performance Conductive Textiles. Issue 8 (27th May 2014) - Wang, Xiaolong; Yan, Casey; Hu, Hong; Zhou, Xuechang; Guo, Ruisheng; Liu, Xuqing; Xie, Zhuang; Huang, Zhifeng; Zheng, Zijian
Abstract This paper describes a fully aqueous‐ and air‐compatible chemical approach to preparing high‐performance conductive textiles. In this method, the surfaces of textile materials are first modified with an aqueous solution of double‐bond‐containing silane molecules to form a surface‐anchoring layer for subsequent in situ free‐radical polymerization of [2‐(methacryloyloxy)ethyl]trimethylammonium chloride (METAC) in the air. Thin layers of poly‐METAC (PMETAC) are therefore covalently grafted on top of the silane‐modified textile surface. Cu‐ or Ni‐coated textiles are finally fabricated by electroless deposition (ELD) onto the PMETAC‐modified textiles. Parameters including polymerization time, temperature, and ELD conditions are studied to optimize the whole fabrication process. The as‐made conductive textiles exhibit sheet resistance as low as 0.2 Ω sq−1, which makes them highly suitable for use as conductive wires and interconnects in flexible and wearable electronic devices. More importantly, the chemical method is fully compatible with the conventional "pad‐dry‐cure" fabrication process in the textile manufacturing industry, thus indicating that it is very promising for high‐throughput and roll‐to‐roll fabrication of high‐performance metal‐coated conductive textiles in the future.